Incomplete Information in Cournot Oligopoly: The Case of Unknown Production Capacities - Jan Richter (Institute of Energy Economics at the University of Cologne (EWI), 2013)
A Cournot oligopoly in which firms face incomplete information with respect to production capacities is studied. For the case where the firms' capacities are stochastically independent, the functional form of equilibrium strategies is derived. If inverse demand is concave, a unique symmetric equilibrium exists, and if demand is linear, then every equilibrium is symmetric. In the case of duopoly, the impact on social welfare when firms commit ex-ante on exchanging information is analyzed. Sharing information increases expected output and social welfare in a large class of models. If the demand intercept is sufficiently large, sharing information increases producer surplus and decreases consumer surplus (and vice versa).
Keywords: C72; D43; L13; 330; Oligopoly; Incomplete Information; Cournot; Capacity Constraints; Information Sharing